Effect of Post-Heat Treatment on Field Emission Properties for Carbon Nanotube Cathodes - Ha, Sang-Hoon; Kwon, Na-Hyun; Song, Pung Keun; Chang, Jiho; Cho, Young-Rae (Journal of the Korean Institute of Metals and Materials, 2010)
For the application of field emission display (FED), it is essential to develop a carbon nanotube (CNT) cathode with high emission current density. In this study, we developed and demonstrated a post-heat treatment (PHT) process to improve field emission properties of CNT cathodes. Since the PHT is intended to burn out organic materials covering the CNTs, the PHT was carried out by heating samples at a high temperature in an atmosphere. The PHT process is applied for samples processed by surface treatment with an adhesive tape. Compared to samples prior to the PHT, samples after the PHT at 360'C showed about 17% improvement in emission current density. The major reason for the increased current density is mainly the increased aspect ratio of the CNTs because of the removal of the adhesive organic residues covering the CNTs, which were attached on the CNT surfaces during the surface treatment using the adhesive taping method.